Development of Local Pig in Indonesia - Soewandi, Bayu Dewantoro Putro; Talib, Chalid (Indonesian Animal Sciences Society, 2015)
Indonesia is a country that has the largest swine germplasm in the world and having five out of eight species, but the population of local pig has been decreasing toward extinction. This paper describes characteristic of local pig and factors that cause endangered of germplasm and strategy to prevent the declined population. One of the factors that causing decreased of local pig population is due to its lower productivity. Government policies for the development of local pigs have not been planned yet because of the socio-cultural barriers. Therefore, establishment of the genetic resource conservation for local pig area is required. In addition, local pig preservation activities can be integrated with the promotion of cultural heritage and local traditions. Development strategy should be planned to increase local pig value, including (1) Build a genetic resource conservation area in the outer islands in Indonesia for wild pigs; (2) Preserving local pigs to develop local pig farms by community; and (3) Integrating maintenance of local pig farm with cultural activities through the establishment of village/tourist area. Keywords: Local pig, characteristic, development